2007
DOI: 10.1097/rlu.0b013e318156b980
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intra-arterial Injected Autologous Bone Marrow Mononuclear Cell Distribution by Radioactive Labeling in Acute Ischemic Stroke

Abstract: Our results showed that Tc-99m HMPAO can be used to label ABMMN cells for in vivo cell visualization, and that brain SPECT imaging with labeled ABMMN cells is a feasible noninvasive method for studying the fate of transplanted cells in vivo. Additionally, our findings demonstrate the localization of these intra-arterially injected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 6 publications
2
42
0
2
Order By: Relevance
“…Although it has been shown that radio-labeling is one of the most sensitive methods for stem cell tracking, we recommended that the application of this tracking technique should be treated with great caution, and if necessary, as little of 111 In-oxine as possible should be added to the cells (or only a limited fraction of the cells should be labeled) to minimize cell loss. Such a conclusion is also confirmed by other similar reported experiments (Correa, Mesquita et al 2007). Hence, in our second experience to track stem cells after intravenous infusion to patients with liver cirrhosis [3], we just labeled 50% of the stem cells.…”
Section: -Spect (Single Photon Emission Computed Tomography)supporting
confidence: 91%
“…Although it has been shown that radio-labeling is one of the most sensitive methods for stem cell tracking, we recommended that the application of this tracking technique should be treated with great caution, and if necessary, as little of 111 In-oxine as possible should be added to the cells (or only a limited fraction of the cells should be labeled) to minimize cell loss. Such a conclusion is also confirmed by other similar reported experiments (Correa, Mesquita et al 2007). Hence, in our second experience to track stem cells after intravenous infusion to patients with liver cirrhosis [3], we just labeled 50% of the stem cells.…”
Section: -Spect (Single Photon Emission Computed Tomography)supporting
confidence: 91%
“…6,8,17 An IA delivery of MNCs through the carotid artery confers more benefit in rats compared with an intravenous approach. 6 While clinical studies outside the United States in patients with stroke have already commenced delivering MNCs into the cerebral arterial circulation, 11 it is important to assess whether MNCs can be damaged with the devices commonly used in the endovascular suite. A recent study assessed the effects of catheter passage of mesenchymal stem cells to the heart and found that higher flow rates did impair gene expression of certain growth factors, which are believed to underlie, in part, the effects of these cells in promoting cardiac repair.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, tested whether catheters, routinely used for IA therapies in acute stroke, impact the viability and function of bone marrow MNCs, a cellular product that has been shown to improve recovery after stroke in animal models 8,9 and is currently being tested in trials involving patients with acute stroke and various cardiac disorders. 2,10,11 Proving that this method of delivery does not alter the viability and function of cells is a crucial step before its full-scale application in clinical safety and efficacy studies involving patients with neurologic disorders such as stroke.…”
mentioning
confidence: 99%
“…More importantly, whole-body imaging provides an estimation of the proportion of injected cells that eventually enter the brain in relation to other organs, to help in the assessment of the functional value of transplantation. SPECT imaging is also truly translational and the same tracers can be used in human studies (Correa et al, 2007;Barbosa da Fonseca et al, 2010). Several studies have compared different administration routes.…”
Section: Effect Of Administration Routementioning
confidence: 99%